Study on internal overvoltages of 220 kV submarine cable transmission system of the offshore oil–gas field group - Han Li; Peixin Yu; Shurong Li; Junbo Deng (Energy Reports, 2022)
Since the Electromagnetic Transient (EMT) process of the high-voltage submarine cable has a great influence on the safe and stable operation of the transmission system, it is necessary to analyze its EMT process under actual engineering. In this study, PSCAD (EMTDC) is used to simulate the internal overvoltages (power-frequency overvoltages and switching overvoltages) of the submarine cable transmission system. Under the working conditions considered in this study, the maximum power-frequency overvoltage in the system occurs in the case of single-phase fault earthing, which is 1.147 p.u. The maximum switching overvoltage is 1.321 p.u., and the 2% overvoltage is 1.276 p.u. The above results are all able to meet the regulations of the internal overvoltages. By simulating the overvoltages in the system, the operation states of the system can be obtained, which is of great significance to improve the transmission reliability of the submarine cable system.